2021
DOI: 10.3390/nano11051328
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling the Potential Role of Nanozymes in Combating the COVID-19 Outbreak

Abstract: The current coronavirus disease 2019 (COVID-19) outbreak is considered as one of the biggest public health challenges and medical emergencies of the century. A global health emergency demands an urgent development of rapid diagnostic tools and advanced therapeutics for the mitigation of COVID-19. To cope with the current crisis, nanotechnology offers a number of approaches based on abundance and versatile functioning. Despite major developments in early diagnostics and control of severe acute respiratory syndr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 98 publications
0
6
0
Order By: Relevance
“…Thus, in indirect ELISA, the conjugated nanozyme is a cost-effective strategy that lowers dependency on basic molecular techniques used for virus detection. 148 Consequently, these nanozymes may function as immunostimulatory substances that provoke protective action against SARS-CoV-2. Therefore, nanozymes having catalase-or superoxide dismutase-like activity can aid in the detoxification of ROS and hence prevent inflammatory and age-related disorders by employing ROS scavenging properties.…”
Section: ■ Nanozymes As Biosensorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, in indirect ELISA, the conjugated nanozyme is a cost-effective strategy that lowers dependency on basic molecular techniques used for virus detection. 148 Consequently, these nanozymes may function as immunostimulatory substances that provoke protective action against SARS-CoV-2. Therefore, nanozymes having catalase-or superoxide dismutase-like activity can aid in the detoxification of ROS and hence prevent inflammatory and age-related disorders by employing ROS scavenging properties.…”
Section: ■ Nanozymes As Biosensorsmentioning
confidence: 99%
“…The nanozymes can also be utilized for enhancing the sensitivity for serological testing, such as ELISA for Covid detection. Thus, in indirect ELISA, the conjugated nanozyme is a cost-effective strategy that lowers dependency on basic molecular techniques used for virus detection . Consequently, these nanozymes may function as immunostimulatory substances that provoke protective action against SARS-CoV-2.…”
Section: Nanozymes-based Disease Therapymentioning
confidence: 99%
“…3) . Thus, Nanozymes have been studied as a successful therapeutic/diagnostic agent for treating this global pandemic in many ways (Ali et al, 2021). Furthermore, since nanomaterials composed of ZnO, AgNPs, Ag nanowires, and glutathione-coated AgS2 nanoclusters have shown anti-viral effects after coronaviruses, the use of these nanomaterials as Nanozymes could also be explored for inhibiting the viral entry inside the host, disrupting its attachment with the spike protein, and blocking the SARS-CoV-2 transcription once it is inside the host cell.…”
Section: A Sars-cov-2 and Other Respiratory Virusesmentioning
confidence: 99%
“…IONPs bind to S1‐RBD to form the most stable complex, which is associated with conformational changes in viral structural proteins and viral inactivation, thereby inhibiting viral entry into host cells. Another study 130 demonstrated that IONPs can inactivate or destroy the virus itself by stimulating lipid peroxidation of the viral envelope. So it is possible that the IONPs inactivation spectrum could also expand.…”
Section: Nanotechnology Indirectly Manages Cs By Inhibiting Sars‐cov‐...mentioning
confidence: 99%